Algorithm for calculating the natural gas flowrate with taking into account the roughness measured in real time - Chaban, Bohdan; Lesovoi, Leonid (Lviv Polytechnic Publishing House, 2016)
The calculation of gas volume flow, reduced to standard conditions, using differential pressure method, was analyzed. New algorithm for calculating natural gas volume flow, reduced to standard conditions, considering the equivalent roughness of the internal surface of the measuring pipeline, measured in real time, was obtained. It will allow to increase the accuracy of measuring natural gas volume flow by differential pressure method.
Keywords: differential pressure method; algorithm of calculation; volume flow; natural gas; roughness